Quirinius’ Sacrifice (Silius Italicus: Punica 4,192–215) - Kozák, Dániel (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
Contrary to historical accounts, Silius inserts a preliminary encounter into his account of the Battle of Ticinus in the Punica in which, prior to facing Hannibal’s army, the Romans fight against the Gauls led by the Boian Crixus (4,143–310). Among Crixus’ victims, we found three soldiers whose names recall early kings of Rome: Tullus, Remulus, and Quirinius. After a brief overview of the significance of these names, the paper focuses on the character of Quirinius (4,192–215). I interpret this episode through three approaches. 1) Quirinius’ death recalls, by inversion, the miraculous survival of L. Sergius Silus (Plin. Nat. 7,104–106), 2) his plan to kill Crixus evokes the ritual of seizing and offering of the spolia opima, while 3) his being certain of impending death makes his case reminiscent of the devotio. Quirinius’ self-sacrifice thus can be seen as contributing to the Elder Scipio’s victory over Crixus, and is also paralleled by how the general’s life will be saved through external help (coming from the gods and his son) in the second half of the battle.